IMPLEMENTATION OF MULTI-PROFESSIONAL EDUCATION: A SHORT REVIEW OF THE RESEARCH METHODOLOGY AND BIOSTATISTICS COURSE - Herry Novrinda (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: The faculty of Dentistry Universitas Indonesia (FDUI) has implemented multiprofessional education (MPE) since the academic year of 2012/2013. Some concerns about facilitators and the achievement of students arose. This study aims (1) to describe the curriculum mapping, (2) to elaborate the perception of facilitators regarding the implementation of MPE, and (3) to assess the achievement among non-MPE and MPE groups in a particular subject.Methods: This research used a quantitative and qualitative approach. This research collected the data of achievement, perception of facilitators, and the curriculum in order to assess the implementation of MPE.Results: The curriculum consisted of common subjects or topics. There were some suggestions regarding the facilitators and the curriculum in the implementation of MPE. In line with one-way Annova, the mean score of students among Non-MPE (76.52±4.36), MPE_2012 (75.52±4.39), and MPE_2013 groups (75.46±4.66) were not statistically different with p-value = 0.154. Conclusion: The faculty has succeeded in compiling an integrated MPE curriculum. There are opportunities for an improvement in several areas. The academic achievement of MPE students is as good as Non-MPE students. The MPE group’s research proposals seemed to have a spirit of collaboration.